2011
DOI: 10.2144/000113589
|View full text |Cite
|
Sign up to set email alerts
|

Rapid DNA amplification in a capillary tube by natural convection with a single isothermal heater

Abstract: Herein we describe a simple platform for rapid DNA amplification using convection. Capillary convective PCR (CCPCR) heats the bottom of a capillary tube using a dry bath maintained at a fixed temperature of 95°C. The tube is then cooled by the surrounding air, creating a temperature gradient in which a sample can undergo PCR amplification by natural convection through reagent circulation. We demonstrate that altering the melting temperature of the primers relative to the lowest temperature in the tube affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 23 publications
(8 reference statements)
0
34
0
Order By: Relevance
“…Diagnostic applications include microRNA profiling, gene expression analysis, pathogen quantification, and cancer diagnostics (2,3 ). There is an ongoing development of novel devices on the basis of capillary systems, microfluidics, point-of-care testing, microbeads, and related technologies (6,(7)(8)(9)(10)(11)(12).…”
Section: © 2014 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Diagnostic applications include microRNA profiling, gene expression analysis, pathogen quantification, and cancer diagnostics (2,3 ). There is an ongoing development of novel devices on the basis of capillary systems, microfluidics, point-of-care testing, microbeads, and related technologies (6,(7)(8)(9)(10)(11)(12).…”
Section: © 2014 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Therefore, without heating and cooling the container repeatedly, reagents circulate spontaneously and then experience three amplification processes at corresponding temperature zones to amply millions of target DNA copy numbers within one hour. Afterward, our research group established a convective capillary PCR (ccPCR) technique [11]. For the purpose of the convenience of liquid handling, the glass capillary tube as a reagent container was used in this platform.…”
Section: Introductionmentioning
confidence: 99%
“…3.1d, e). More recently, capillary convective PCR platforms have been introduced that impose vertical thermal gradients via heating the side walls of thin capillary tubes containing the PCR reagent mixture [18][19][20] (Fig. 3.1f).…”
Section: Introductionmentioning
confidence: 99%
“…Closed-loop convective systems have also been demonstrated that transport reagents between PCR temperature zones in (d) oval [8] and (e) triangular [14] flow loops. (f) Thermal convection in capillary tubes heated from below has also been harnessed to perform PCR thermocycling [18]. Panel (a) reprinted with permission from Ref.…”
Section: Introductionmentioning
confidence: 99%